RELATIVITAS PENILAIAN MORAL DALAM PERSPEKTIF AKIDAH DAN FILSAFAT ISLAM - Wira Alvin Al Ghiffary; Irwandra irwandra; Saifullah Saifullah; Aninda Nurfadilah (MAHABBAH: Jurnal Ilmu Ushuluddin Dan Pemikiran Islam, 2026)
This article discusses the relativity of moral judgment from the perspective of Islamic creed (aqidah) and Islamic philosophical thought. The main problem addressed in this study is how Islam views differences in judgments of good and evil in human life and to what extent moral relativity is acknowledged without negating absolute values. This research employs a qualitative method using a library research approach by analyzing primary sources such as the Qur’an, Hadith, and works of Muslim scholars and philosophers, as well as secondary sources including relevant books and academic journal articles. Data were analyzed descriptively and analytically to examine the relationship between revelation and reason in shaping moral values. The findings indicate that Islam recognizes the existence of moral differences at the practical level, influenced by social, cultural, and rational contexts. However, Islamic creed emphasizes that the ultimate standard of good and evil is derived from Allah SWT as an objective and absolute value. Islamic philosophy functions as a rational framework that bridges revealed values with the realities of human life. Therefore, moral relativity in Islam is not absolute but remains bound to transcendental principles rooted in Islamic creed. This study concludes that the integration of aqidah and Islamic philosophical thought produces a balanced moral concept between absolute values and human life dynamics.